EVALUATION OF RENAL CHANGES IN SICKLE CELL DISEASE IN A REFERRAL GOVERNMENT INSTITUTE OF SOUTHERN ODISHA - BEHERA, BIJAYA KUMAR; BEHERA, SUSANTA SEKHAR; JENA, SUKANTA KUMAR; MOHANTY, RAKESH; BEHERA, NISARG (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study was to study various renal manifestations in sickle cell disease (SCD) and to establish a cause and effect relationship with the evaluation of risk factors. Methods: This prospective observational cross-sectional study was conducted on 82 SCD patients belonging to the age group of 15–50 years of both the genders over a period of 2 years from January 2019 to December 2020 in MKCG Medical College and Hospital, Berhampur, Odisha, India. Eighty-two patients, 32 (39.02%) having sickle cell anemia (SCA) and 50 (60.98%) having sickle cell trait (SCT), admitted to medicine and nephrology wards of the hospital were included in this study. SCD patients with other hemolytic anemia and with renal congenital/structural abnormality and patients with systemic diseases such as diabetes mellitus, systemic hypertension, and systemic lupus erythematosus were excluded from the study. Various laboratory investigations such as complete blood count, hemoglobin (Hb), serum sodium, serum potassium, serum urea, serum creatinine, fasting blood sugar, erythrocyte sedimentation rate, liver function test, urine routine, and microscopic test were carried out. Diagnosis of SCD patients was based on sickling test and high-performance liquid chromatography testing. Radiologic imaging (Sonography for renal changes) was done at radiodiagnosis department of the hospital. Results: Glomerular and tubular dysfunction was more in SCA (Hb SS) patients than SCT (Hb AS) patients and the abnormality was more in patients in crisis. Albuminuria in 78.12%, hematuria in 46.87%, cast and crystal in 28.12%, epithelial cell in 31.25%, and hyposthenuria in 56.25% were found in SCA patients. In SCT patients, albuminuria in 38%, hematuria in 16%, cast and crystal in 22%, epithelial cell in 12%, and hyposthenuria in 24% were found. All the above findings were more in percentages in crisis patients of both the groups. In SCA, 37.5% and in SCT, 2% were found to have chronic kidney disease. Conclusion: Renal involvement in the form of glomerular and tubular dysfunction occur in SCD and more in crisis patients, leading to renal complications, and end-stage renal disease.